Temperature Matters: Bacterial Response to Temperature Change - Moon, Seongjoon; Ham, Soojeong; Jeong, Juwon; Ku, Heechan; Kim, Hyunhee; Lee, Changhan (Journal of Microbiology, 2023)
Temperature is one of the most important factors in all living organisms for survival. Being a unicellular organism, bacterium requires sensitive sensing and defense mechanisms to tolerate changes in temperature. During a temperature shift, the structure and composition of various cellular molecules including nucleic acids, proteins, and membranes are affected. In addition, numerous genes are induced during heat or cold shocks to overcome the cellular stresses, which are known as heat- and cold-shock proteins. In this review, we describe the cellular phenomena that occur with temperature change and bacterial responses from a molecular perspective, mainly in Escherichia coli.
Keywords: Bacteria; Bacterial Proteins; Cold Temperature; Escherichia coli; Escherichia coli Proteins; Hot Temperature; Temperature; Chaperone; Cold shock; Cold shock protein; Heat shock; Heat shock protein; Thermosensor